2021
DOI: 10.1242/dmm.049068
|View full text |Cite
|
Sign up to set email alerts
|

A mechanism linking perinatal 2,3,7,8 tetrachlorodibenzo-p-dioxin exposure to lower urinary tract dysfunction in adulthood

Abstract: Benign Prostatic Hyperplasia / Lower Urinary Tract Dysfunction (BPH/LUTD) is a classic disease of aging which affects nearly all men. Symptoms typically present in the fifth or sixth decade and progressively worsen over the remainder of life. Here, we identify a surprising origin of this disease that traces back to the intrauterine environment of the developing male, challenging existing paradigms about when this disease process begins. We delivered a single bolus dose of a widespread environmental contaminant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 87 publications
0
7
0
Order By: Relevance
“…Increasing evidence suggests that exposure to environmental toxicants can contribute to lower urinary tract function in adulthood. Developmental exposure to environmental toxicant, dioxin (TCDD) via the dam, has been shown to decrease void intervals in adult male mouse offspring [ 63 ] and further exacerbates voiding dysfunction in susceptible mice [ 64 , 65 ]. There is also evidence that remodeling of collagen is one pathway by which environmental chemicals can impact the lower urinary tract.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence suggests that exposure to environmental toxicants can contribute to lower urinary tract function in adulthood. Developmental exposure to environmental toxicant, dioxin (TCDD) via the dam, has been shown to decrease void intervals in adult male mouse offspring [ 63 ] and further exacerbates voiding dysfunction in susceptible mice [ 64 , 65 ]. There is also evidence that remodeling of collagen is one pathway by which environmental chemicals can impact the lower urinary tract.…”
Section: Discussionmentioning
confidence: 99%
“…Factors responsible for severe drug-refractory disease are not understood. Recent studies reveal potential roles for environmental chemical exposures, during the fetal period when the lower urinary tract is developing [19][20][21] and during other stages, in driving LUTD susceptibility and progression, opening an entirely new line of toxicology research towards understanding environmental factors that contribute to LUTD processes. This review is intended as a resource for toxicologists and other discipline specialists who are considering entry into the urologic disease research space and wishing to examine LUTD as a toxicology research endpoint.…”
Section: Ultrasound Ultrasoundmentioning
confidence: 99%
“…There is emerging evidence that environmental chemicals can also change prostatic innervation to cause prostatic smooth muscle dysfunction, specifically by acting during the fetal and neonatal periods when prostate autonomic innervation is established. For example, we recently showed in C57BL/6J mice that gestational exposure to the widespread environmental contaminant TCDD (a single 1 µg/kg oral maternal dose on the 13th day of gestation) increases noradrenergic fiber density (nerve terminals) in the prostate of male mouse fetuses without changing the density of cholinergic or peptidergic fibers [160]. TCDD-induced prostatic noradrenergic hyperinnervation persists into adulthood and is coupled to hyperactivity of prostatic smooth muscle and abnormal urinary function in mice, including increased urinary frequency [160].…”
Section: Benign Prostatic Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…A better understanding of causative agents which trigger these changes in prostatic growth or morphology could improve the ability to diagnose and treat a subset of patients suffering from LUTD. Increasing evidence suggests that early life exposure to environmental contaminants can influence prostate development, growth, and the onset and progression of abnormal voiding physiology in rodent models [ 7 , 8 , 9 , 10 , 11 ]. We have previously shown that young adult mice (6–7 weeks of age) exposed to polychlorinated biphenyls (PCBs), a ubiquitous environmental contaminant, through gestation and lactation display smaller, more frequent voiding phenotypes that were sex and dose-dependent [ 12 ].…”
Section: Introductionmentioning
confidence: 99%